2016
DOI: 10.1002/2015gl066686
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term probabilistic earthquake risk assessment considering time‐dependentbvalues

Abstract: Laboratory experiments highlight a systematic b value decrease during the stress increase period before failure, and some large natural events are known to show a precursory decrease in the b value. However, short‐term forecast models currently consider only the generic probability that an event can trigger subsequent seismicity in the near field. While the probability increase over a stationary Poissonian background is substantial, selected case studies have shown through cost‐benefit analysis that the absolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 53 publications
5
48
2
Order By: Relevance
“…Note also the 10% decrease in b value during the months to days prior to the mainshock. While this anomaly is consistent with selected case studies and laboratory studies that have reported dropping precursory b values (Gulia et al, ; Papadopoulos et al, ; Tormann et al, ), the number of premainshock stacked time series is only 8.…”
Section: Resultssupporting
confidence: 89%
“…Note also the 10% decrease in b value during the months to days prior to the mainshock. While this anomaly is consistent with selected case studies and laboratory studies that have reported dropping precursory b values (Gulia et al, ; Papadopoulos et al, ; Tormann et al, ), the number of premainshock stacked time series is only 8.…”
Section: Resultssupporting
confidence: 89%
“…After the M L = 4.1 event, rate and magnitude of foreshocks increased and seismicity migrated toward the main shock nucleation zone. Gulia et al (2016) studied a circular area of 20 km radius, centered on the mainshock epicenter. They observed that a foreshock sequence started 3 months before the mainshock, activating a region of about 10 km length.…”
Section: Discussionmentioning
confidence: 99%
“…The mainshock was followed by abundant aftershocks, with the major events occurring on 7 April (M w = 5.6) and on 9 April (M w = 5.4). Immediately following the mainshock, Marzocchi and Lombardi (2009) began producing daily aftershock forecasts based on a stochastic model that combines the G-R (Gutenberg and Richter, 1944) distribution and space-time power-law decay of triggered shocks.…”
Section: E Daskalaki Et Al: Foreshocks and Short-term Hazard Assessmentioning
confidence: 99%
See 1 more Smart Citation
“…We use the rich earthquake record along the Pacific Plate off Japan and investigate spatial NRP distributions and temporal changes for different target magnitudes. It is evident from seismicity records that earthquake activity (expressed by the a value in the Gutenberg-Richter law) changes greatly through space and time, and there is also plenty of evidence for significant spatiotemporal variability in the relative fraction of small to large magnitudes (expressed by the b value in the Gutenberg-Richter law) [e.g., Wiemer and Wyss, 1997;Enescu and Ito, 2001;Schorlemmer et al, 2004;Nanjo et al, 2012;Tormann et al, 2012Tormann et al, , 2013Gulia et al, 2016]. In particular, a recent study [Tormann et al, 2015] has documented a remarkable change in the size distribution of earthquakes along the Pacific Plate off Japan before and after the Tohoku event.…”
Section: Introductionmentioning
confidence: 99%